2022
DOI: 10.3390/ijms23095146
|View full text |Cite
|
Sign up to set email alerts
|

Lipotoxicity as the Leading Cause of Non-Alcoholic Steatohepatitis

Abstract: The emerging issues nowadays are non-alcoholic fatty liver disease (NAFLD) and its advanced stage non-alcoholic steatohepatitis (NASH), which further can be a predisposing factor for chronic liver complications, such as cirrhosis and/or development of hepatocellular carcinoma (HCC). Liver lipotoxicity can influence the accumulation of reactive oxygen species (ROS), so oxidative stress is also crucial for the progression of NASH. Moreover, NASH is in strong connection with metabolic disorders, and supporting ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 169 publications
0
29
0
Order By: Relevance
“…Steatosis is characterized by the accumulation of triglycerides (TGs) as a compensatory response to an increase in free fatty acids (FFAs) within the cell. Moreover, the FFAs are partitioned into an inert and stable lipid, preventing the injury of hepatocytes ( Kawano and Cohen, 2013 ; Branković et al, 2022 ). As a matter of fact, there have been abundant reviews of the mechanisms underlying steatosis development elsewhere.…”
Section: Inflammation and Fibrosis In Nafldmentioning
confidence: 99%
“…Steatosis is characterized by the accumulation of triglycerides (TGs) as a compensatory response to an increase in free fatty acids (FFAs) within the cell. Moreover, the FFAs are partitioned into an inert and stable lipid, preventing the injury of hepatocytes ( Kawano and Cohen, 2013 ; Branković et al, 2022 ). As a matter of fact, there have been abundant reviews of the mechanisms underlying steatosis development elsewhere.…”
Section: Inflammation and Fibrosis In Nafldmentioning
confidence: 99%
“…Studies have shown that the frequency of developing liver cirrhosis in patients with NAFLD increases with age and that patients older than 50 years are at a higher risk for developing severe fibrosis [ 118 , 119 ]. NAFLD has a tendency to progress to NASH which is associated with obesity, metabolic syndrome, type 2 diabetes, insulin resistance and cardiovascular diseases [ 120 ]. The frequency of most of the mentioned conditions increases with age [ 3 ].…”
Section: Liver Diseases and Agingmentioning
confidence: 99%
“…As the incidence of non-alcoholic fatty liver disease (NAFLD) is galloping, it is crucial to focus on it as an emerging issue, since it could progress to non-alcoholic steato-hepatitis (NASH) which can be a further predisposing factor for chronic liver complications [ 7 ]. NAFLD frequently overlaps with one or more elements of metabolic syndrome including obesity, insulin resistance, dyslipidemia, and arterial hypertension [ 8 ], which all are known to have a significant impact on the severity of COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%